Performance of Dual-tracer PET-CT for Staging Post–Liver Transplant Hepatocellular Carcinoma Recurrence. Issue 10 (October 2021) - Au, Kin-Pan; Dai, Wing-Chiu; Chi-Yan Chan, Albert; Cheung, Tan-To; Lo, Chung-Mau; Chok, Kenneth Siu-Ho
Abstract : Background: Precise staging is essential in the management of patients with recurrent hepatocellular carcinoma (HCC) after liver transplantation. There is no current consensus on the optimal staging strategy. We conducted this study to evaluate the performance of dual-tracer positron emission tomography-computed tomography (PET-CT) for this purpose and to investigate whether the results of dual-tracer PET-CT affected patient management. Methods: A retrospective study was conducted. Patients who underwent dual-tracer PET-CT for suspected or confirmed HCC recurrence after liver transplant were included. The lesion-based sensitivity and positive predictive value of dual-tracer PET-CT were determined. Results: Fifty-six patients and 189 recurrent tumors were included. The lesion-based sensitivity and positive predictive value of dual-tracer PET-CT were 94.7% and 90.4%, respectively. The sensitivity of dual-tracer PET-CT was better than the standard imaging in the surveillance protocol (82.5% versus 94.7%, P < 0.001), especially for detecting liver recurrence (71.0% versus 96.8%, P < 0.001). Half of the dual-tracer PET-CT detected additional recurrence (n = 26, 46.4%) and one-third led to a change in management (n = 19, 33.9%). Ten patients (17.9%) with inconclusive standard imaging had metabolic recurrence confirmed on PET-CT and treatment was commenced early. Four patients (7.1%) had revised locoregional treatment, and 5 (8.9%) had to withdraw from locoregional treatment after the detection of additional metastatic disease. Conclusions: Dual-tracer PET-CT is effective for staging posttransplant HCC recurrence. It often provides valuable information to guide clinical management.